University choice: The role of expected earnings, non-pecuniary outcomes and financial constraints - Adeline Delavande; Basit Zafar (University of Essex, Institute for Social and Economic Research (ISER), 2014)
We investigate the determinants of students' university choice, with a focus on expected monetary returns, non-pecuniary factors enjoyed at school, and financial constraints, in the Pakistani context. To mitigate the identification problem concerning the separation of preferences, expectations and markets constraints, we combine rich data on individual-specific subjective expectations about labor market and non-pecuniary outcomes, with direct measures of financial constraints and students' stated school choice both with and without financial constraints. Estimates from a life-cycle model show that future earnings play a small (but statistically significant) role. However, non-pecuniary outcomes, such as school's ideology, are major determinants. Data on students' choices without financial constraints allow for the outof-sample validation of the model, which shows a strikingly good fit. Our results show that 37% of students are financially constrained in the university choice, and that implementing policies relaxing financial constraints would increase students' average lifetime subjective expected utility by 21%. From a methodological point, we find that ignoring non-pecuniary factors, uncertainty related to employment and drop-out, or direct measures of financial constraints, yields biased estimates - thereby underscoring the importance of having data on these aspects for understanding university choice in any context.
Keywords: D81; D84; I21; I23; 330; school choice; credit constraints; subjective expectations